Results of Implementation of Preventive Recommendations for Tuberculosis After Renal Transplantation in an Endemic Area. Issue 12 (1st October 2013) - de Lemos, A. S.; Vieira, M. A. M. S.; Halpern, M.; Quaresma, R. G.; Borchardt, A. C.; Santos, M. A. A. R.; Gonçalves, R. T.; Santoro‐Lopes, G.
<x xml:space="preserve">Abstract</x> This retrospective cohort study assessed the results of the implementation of preventive recommendations for tuberculosis (TB) among renal transplant recipients in an endemic area (Rio de Janeiro, Brazil). Subjects were defined as at high risk for TB if they had latent tuberculosis infection (LTBI), reported recent close contact with individuals with TB or received a graft from a donor with LTBI. A 6‐month course of isoniazid preventive therapy (IPT) was targeted to high‐risk subjects. The study end point was TB confirmed by culture. Altogether, 535 patients were included. Median follow‐up was 59 months. The overall cumulative incidence of TB was 2.1% while among the 274 patients in whom the preventive protocol was fully implemented, the incidence was only 0.7%. The incidence of TB among 75 high‐risk recipients not treated with isoniazid (7%) was significantly higher than that observed in 209 untreated low‐risk patients (1%, p = 0.006) and in 65 high‐risk subjects that received IPT (no case, p = 0.03). In conclusion, the implementation of preventive recommendations for TB in an endemic area allowed the appropriate discrimination between high‐ and low‐risk renal transplant recipients and was associated with long‐term reduction in the incidence of this complication among high‐risk subjects.